Pengaruh Pemberian Insentif Terhadap Kinerja Karyawan Pada Perusahaan Pabrik Gelas di Gowa - Roswiyanti Roswiyanti; Mattarima Mattarima (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The incentive is a reward or retribution provided the company to employees who perform as a form of reward. Incentives as a means of motivation that encourages employees to work with optimal ability, which was intended as an extra income outside of salary or wages have been determined. The incentive is a driving factor for the employees to work better so that the employee's performance can be increased. The granting of incentives are intended to meet the needs of the employees. This research using qualitative research methods. As for the independent variable Incentive (X) and the dependent variable (Y) Performance. The population in this research is the Production Department glass manufacturing company. The sample used in this dipenelitian is saturated sample in which every Member of the population serve as samples. In this study, data gathering is carried out using a questionnaire. Based on the results of the determination of the calculation can be seen that the value of R2 is 0.907 Adusted. This can indicate the magnitude of the role or contribution that independent variable (X1), namely incentive can explain or influence the dependent variable (Y) the performance of employees amounted to 95.2%, while the rest is affected by other factors that do not researched. And based on the results of testing linearity obtained value p value of 0.05 0.00 < Sig. This indicates acceptance of the H1 so that the relationship can be inferred variable x with y Linear.